Simultaneous Cervical and Lumbar Spine Surgery: Retrospective Analysis of 45 Cases - Aiwale, Amit Babasaheb; Patel, Pankajkumar Ranchhodbhai; Paspala, Syed Ameer Basha; Murthy, T. V. Ramakrishna (Indian Journal of Neurosurgery, 2019)
Background The term ‘tandem spinal stenosis’ (TSS) was first introduced by Dagi et al to describe concurrent symptomatic cervical and lumbar spinal stenosis. A typical clinical picture includes intermittent neurogenic claudication, myelopathy, and polyradiculopathy in both the upper and lower extremities. The incidence of TSS ranges from 0.12 to 28%.Methods We studied patients who presented with tandem canal stenosis and operated cervicolumbar decompression with or without fusion procedures by two separate neurosurgical teams simultaneously from June 2015 to 2017 with follow-up period of minimum 6 months.Results We had 30 (66.66%) male and 15 (33.33%) female patients who underwent simultaneous cervical and lumbar spine surgeries. The average age was 57.8 years (male) and 53.9 years (female). Cervical canal stenosis was graded as per magnetic resonance imaging (MRI) morphological grades of stenosis by Kang et al and lumbar grading, was done as per Schizas et al grading system. The mean duration of complaints in cervical and lumbar compression was 29.54 ± 44.99 months and 30.55 ± 38.11 months, respectively. The mean preoperative Japanese Orthopaedic Association (JOA) score of was 10.46 ± 1.39, whereas the postoperative mean JOA score was 11.93 ± 1.28, and mean preoperative (38.59 ± 16.52) and postoperative (29.22 ± 9.38) Oswestry Disability Index (ODI) scores showed a statistically significant difference (p = 0.0001).Conclusion Patients with TSS are elderly and have associated comorbidities, still simultaneous cervical and lumbar surgery is feasible with the good outcome if you have two neurosurgical teams operating simultaneously and having good other super specialty teams’ support. It can be timesaving and cost effective for patients. Also, it avoids patients from undergoing exposure to two separate surgical and anesthetic stress.
Keywords: tandem spinal stenosis; simultaneous cervicolumbar; spine surgery